Democratizing Domain-Specific Computing: Creating a programming environment and compilation flow that empowers programmers to create their own DSAs efficiently and affordably on FPGAs. - YUZE CHI; WEIKANG QIAO; SOHRABIZADEH, ATEFEH; JIE WANG; CONG, JASON (Communications of the ACM, 2023)
The article discusses creating an environment in which computer programmers are empowered to design domain-specific accelerators (DSAs) through an automated process. DSAs have been shown to deliver higher performance and greater energy efficiency in customized computing systems than general purpose central processing units (CPUs). Field programmable gate arrays (FPGAs) are discussed as viable alternatives to application-specific integrated circuits (ASICs) which are cost prohibitive.